Causes of Exclusion of a Living Kidney Donor in a Public Hospital in a Developing Country. (July 2018) - Taylor, Marcelo; Ciappa, Julio M; Mir, German; Barcos, Amilcar
Abstract : Introduction: Since the constant increase in the frequency of V stage chronic renal failure and due to the limited availability of cadaveric organs, the living donor it's considered as a viable solution. However, there are many causes that caution against the living donor. MaterialsandMethods: All donors who presented themselves voluntarily to our service to get tested as living kidney donor between the 1st of April 2016 and the October the 31th, were considered. There were analyzed all reasons of exclusion for donation. Results: An overall of 276 subjects presented to get tested in our unity, 186 of them (67.39%) were discarded as donors. Almost half of them (40, 86%) were discarded for no donor reasons; the most frequent reason was the desertion of the donor during the evaluation. Of the 128 donors left, there were found 240 causes of contraindication for donation. Medical causes are detailed in chart 1. Most of the discarded patients showed more than one contraindication for donation (n=68, 53.12%). Conclusion: More than half (67.39) of applicants for living kidney donor were discarded of donation. Half of the for no medical reasons, where the disinformation may have had a major role, whereas the other half of the patients, who were considered healthy, were found pathologies which indicated not only the exclusion to donate but also the requirement of a medical follow-up.